Decomposition dynamics of Myrtus communis and Quercus ilex leaf litter: Mass loss, microbial activity and quality change - Fioretto, A.; Papa, S.; Pellegrino, A.; Fuggi, A. (Applied Soil Ecology, 2007)
The patterns of microbial respiration and enzyme activity (cellulase, xylanase, laccase and peroxidase) in the leaf litter of two evergreen sclerophyll species, Myrtus communis and Quercus ilex, were compared during decay in a low shrubland and in a coppice wood in a Natural Reserve in the Mediterranean area. The two litter types had similar initial amounts of lignin, cellulose and acid-detergentsoluble substances, but the litter from M. communis had a lower N content and higher C/N ratio. In spite of this, the decomposition rate of M. communis litter was higher than for Q. ilex. Whilst no seasonal variation was observed in the rate of organic matter degradation, respiration and extractable cellulase and xylanase activities showed seasonal variation in both litter types with the highest values in winter–early spring and the lowest in summer, and showed positive correlations with water content. Peroxidase activity exhibited a seasonal pattern and was higher in Q. ilex than in M. communis, while laccase activity was higher in M. communis and increased with fungal biomass as degradation progressed. Nevertheless, no relationship was found between laccase and peroxidase activity and lignin degradation. The results obtained indicate that the seasonal alternation of moist and dry periods is the major factor inﬂuencing soil biological activity in the Mediterranean area. The occurrence of pronounced seasonal variation in litter enzyme activity prevents the determination of possible correlations with litter mass loss.
Keywords: Cellulose; Enzyme activity; Fungal biomass; Lignin; litter decomposition; Microbial respiration